Tuition fees at the University of Cape Town: 1923–2020 - Davidson, K.; van Walbeek, C.; Vellios, N. (South African Journal of Higher Education, 2021)
Tuition fees at South African universities have been increasingly contested in recent years. In this article, we analyse trends in tuition fees for five degrees offered by the University of Cape Town (UCT) from 1923 to 2020. Data were collected from UCT’s handbooks and calendars. Adjusting for inflation, we found that, on average, tuition fees increased nearly 400 per cent from 1923 to 2020. Tuition fees increased only marginally between 1923 and 1970, but increased almost 300 per cent, on average, from 1970 to 2020. We also estimated the affordability of tuition fees between 1946 and 2019. Affordability considers both changes in tuition fees and changes in average income, approximated by per capita GDP. Between 1946 and the early 1980s, tuition at UCT became relatively more affordable as the growth in average income generally exceeded the growth in tuition fees. Post-1980, the combination of modest economic growth and rapid increases in tuition fees has made university education at UCT substantially less affordable. The percentage of per capita GDP required to study at UCT doubled between the early 1980s and 2019.